Measuring economic distress using the contingent claims approach - Olli Castrén; Raphael M. Kopp (European Banking Authority (EBA), 2025)
We introduce a new Economic Distress Index (EDI), which incorporates information from all economic sectors as a device for real-time monitoring of financial stability risks in the euro area. Our approach is based on structural models of credit risk and incorporates market and balance sheet information from which we derive distance-to-defaults as uniform risk indicators across economic sectors, which form the basis of the EDI. Monetary financial institutions are the largest contributors to the EDI over the period from 1999 to 2023. In the post-Global Financial Crisis period, non-bank financial intermediaries emerge as the largest contributors to the EDI, consistent with broader developments that have contributed to the growth of non-bank financial intermediation. Using local projections, we show that the EDI also has significant predictive power for macroeconomic developments that originate primarily from high-stress regimes. Finally, we unpack that volatility is clearly the most important driver of the raw risk indicators, accounting on average for almost 80% of the explained variation.
Keywords: C43; C53; E01; E37; E44; G01; 330; Credit risk; Financial accounts; Contingent claims analysis; Systemic risk; Macro-prudential analysis; financial risk; financial stability; risk management; insurance claim; macroeconomics; economic indicator